2020
DOI: 10.1002/nau.24383
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term tadalafil administration can prevent functional and structural changes of the urinary bladder in male rats with partial bladder outlet obstruction

Abstract: Aims There have been few reports on whether long‐term oral phosphodiesterase 5 inhibitor administration can ameliorate bladder changes due to bladder outlet obstruction (BOO). Therefore, we clarified the chronological changes of the bladder using male BOO rats and evaluated the effects of tadalafil on these changes. Methods Eight‐week‐old male Sprague‐Dawley rats were used. BOO was created by placing a polyethylene catheter around the urethra. Then, the rats were orally treated with a vehicle, or tadalafil 2 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
2
2
0
Order By: Relevance
“…In the present study, urethral ligation reduced in vitro contraction responses in detrusor smooth muscle to carbachol, EFS, ATP and KCl. Furthermore, in the current study, tadalafil treatment partially prevented reduced contractile responses in the obstructed bladder, similar to an earlier study (3). On the other hand, decreased contractility of isolated bladder strips was considerably potentiated by NaHS alone.…”
Section: B Asupporting
confidence: 91%
See 2 more Smart Citations
“…In the present study, urethral ligation reduced in vitro contraction responses in detrusor smooth muscle to carbachol, EFS, ATP and KCl. Furthermore, in the current study, tadalafil treatment partially prevented reduced contractile responses in the obstructed bladder, similar to an earlier study (3). On the other hand, decreased contractility of isolated bladder strips was considerably potentiated by NaHS alone.…”
Section: B Asupporting
confidence: 91%
“…NO has a crucial physiological role in the proliferation and differentiation of several cell types and can act as a neurotransmitter in the urothelium and affect bladder function (3,26). However, the relation between the expression levels of NOS isoforms in bladder function remains unclear.…”
Section: B Amentioning
confidence: 99%
See 1 more Smart Citation
“…Motivated by the application to BPH, this project used male rats to produce the BOO condition underlying male LUTS ( Zvara et al, 2002 ). A recent study also reported that this male BOO model exhibits the early hypertrophy-compensation phase followed by the later decompensation phase of bladder dysfunction, similar to those observed in human BPH/BOO ( Shinkai et al, 2020 ).…”
Section: Discussionsupporting
confidence: 76%